Numerical analysis of the reverse blocking enhancement in High-K passivation AlGaN/GaN Schottky barrier diodes with gated edge termination. (February 2018) - Bai, Zhiyuan; Du, Jiangfeng; Xin, Qi; Li, Ruonan; Yu, Qi
Abstract: We conducted a numerical analysis on high-K dielectric passivated AlGaN/GaN Schottky barrier diodes (HPG-SBDs) with a gated edge termination (GET). The reverse blocking characteristics were significantly enhanced without the stimulation of any parasitic effect by varying the dielectric thickness d ge under the GET, thickness T P, and dielectric constant ε r of the high-K passivation layer. The leakage current was reduced by increasing ε r and decreasing d ge . The breakdown voltage of the device was enhanced by increasing ε r and T P . The highest breakdown voltage of 970 V and the lowest leakage current of 0.5 nA/mm were achieved under the conditions of ε r = 80, T P = 800 nm, and d ge = 10 nm. C-V simulation revealed that the HPG-SBDs induced no parasitic capacitance by comparing the integrated charges of the devices with different high-K dielectrics and different d ge . Highlights: A novel AlGaN/GaN SBD with high-K passivation (HPG-SBD) is proposed and analyzed by numerical method. The proposed HPG-SBDs can enhance the reverse blocking characteristics. The proposed HPG-SBDs can achieve a reverse leakage current of 0.5 nA/mm. The BV of HPG-SBDs can be improved from 355 V to 970 V. HPG-SBDs induce no parasitic effects by comparison of integrated charges.